Evaluation of the Financial Performance between Traditional Private Commercial Banks and Islamic Banks in Bangladesh - Akber, S. M.; Dey, Asha (International Journal of Islamic Banking and Finance Research, 2020)
The paper analyzes and evaluated the performance of Islamic banks and Traditional private commercial banks in Bangladesh with a duration from 2015 to 2019. The basis of the analysis used in this paper is CAMEL test.  All the relevant data has collected from the bank’s websites. To measure and compare the performance this paper has used a sample of five Islamic banks and five Traditional private commercial banks. It considered the average ratio of each year.  A standard test format (CAMEL tests) has used to analyze the performance of Islamic and Traditional private commercial banks. To justify the reliability of the data this paper has used t-tests. The outcome of this paper says that apart from the quality of the management significant difference doesn’t exist between the performance of Islamic Banks and Traditional private commercial banks in Bangladesh based on CAMEL test. Considering the quality of the management and asset quality Traditional private commercial banks perform better, but for the capital adequacy and liquidity position Islamic banks perform better in Bangladesh.